HUMAN BEING AND SOCIAL ENTITY IN CONTEMPORARY SOCIAL TRADITION: A COMPARATIVE FRAMEWORK - Andhika Riyadi; Sonny Yuliar (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2023)
Understanding the existential relation between human being and social entity has been a major theme in human sciences. Such an intellectual enquiry is not only important for theoretical purposes, but also of highly relevant for practical life. Within the Western contemporary social sciences, two distinct approaches have recently been attracting wide attention, namely the critical realism and the actor-network theory. The critical realism seeks to explore the interaction mechanism between human subjective individualand its surrounding objective social structure by ascribing independent existential status to each of them, i.e., the subjective existence and the objective existence. In opposite to this, the actor-network theory denies the independent existence of the subject and the object altogether. For actornetwork theory, the question of existence should be answer by tracing the relations that are performed, or enacted, by human individual agents. In other words, existence is relational and performative. Within the Islamictraditions, the works of Ibn Khaldun have been highly respected as a major contribution in the understanding of human being and social behavior and structure. In his Muqaddimah, Ibn Khaldun asserts that human being is inherently political, and human individuals cooperation is fundamental to their collective existence. The aim of the paper is to present a conceptual framework in which the above-described theoretical works could be put side-by-side in such a way as to gain a theoretical synthesis. In this way, we hope that the paper could contribute to the theme of Islamic human sciences by way of dialog between Western and Islamic traditions.